RESULTS OF CORRECTION OF PARTIAL ANOMALOUS PULMONARY VEIN DRAINAGE - Abrolov H.K; Mamatov M.A; Kholmurodov A.A (Scholar Express Journals, 2023)
The paper presents the materials of patients with partial anomalous pulmonary drainage operated on from 2001 to 2021 in the Department of Congenital Heart Disease Surgery of V.Vakhidov RSNPMCh, the age of patients was 1,4-45 years. The diagnosis of the defect was based on the analysis of the combined data of clinical and special methods of investigation. Surgical correction of malformation was performed by median sternotomy and right lateral thoracotomy, with artificial circulation. Peculiarities of the course of the postoperative period depending on the type of malformation were performed. Changes in cardiac parameters were analyzed using electrocardiography, echocardiography and roentgenography.
Keywords: partial anomal perfusion of pulmonary veins; surgical treatment; pulmonary hypertension